Social competence of teachers and students: the case study of Belgium and Lithuania - Gedvilienė, Genutė (Vytautas Magnus University, 2012)
In this study is presented a theoretical concept of social competence and practical quantitative international research conducted in Belgium and Lithuania. Comparative analysis of research was done between Belgium and Lithuania students and teachers' in communication and cooperation skills. In this study is presented detailed investigations.